Simplified steps for managing avulsed permanent tooth - Ismail, Ahmad Faisal; Abdul Hamid, Norsalsabila Hanis; Abdul Shukur, Nur Dini (2021)
This video shows the clinical steps in the management of permanent anterior tooth avulsion, especially in children. The simplified steps are based on the recent recommendation and guidelines,